Cytogenetic examination - Risanto Siswosudarmo, Risanto Siswosudarmo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1981)
Cytogenetic examination on six normal persons, four men and two women, was carried out using a technique proposed by Dutrillaux with slight modification. Five drops of blood were taken from a peripheral vessel and was incubated on a PHA (phytohemarglutinine)-containing medium at 37ÃÂ°C for about 72 hours. Cell division was blocked by adding colchicine solution, an antimitotic agent, into this medium. A mixture of distilled water, magnesium chloride, hyaluronidase, and goat serum was used as hypotonic shock solution. Two out of these six examinations showed good results. The possibility of using this technique to examine some clinical syndromes, such as Down, Turner, and Klinefelter syndromes, as well as 13 and 18 trisomies, has also been discussed.Key Words: cytogenetics - chromosome - blood culture - colchicine - hypotonic shock solution